Open(ing) Access: Top Health Publication Availability to Researchers in Low- and Middle-Income Countries - John L. Kilgallon; Saumya Khanna; Tanujit Dey; Timothy R. Smith; Kavitha Ranganathan (Ubiquity Press, 2023)
Introduction: Improving access to information for health professionals and researchers in low- and middle-income countries (LMICs) is under-prioritized. This study examines publication policies that affect authors and readers from LMICs. Methods: We used the SHERPA RoMEO database and publicly available publishing protocols to evaluate open access (OA) policies, article processing charges (APCs), subscription costs, and availability of health literature relevant to authors and readers in LMICs. Categorical variables were summarized using frequencies with percentages. Continuous variables were reported with median and interquartile range (IQR). Hypothesis testing procedures were performed using Wilcoxon rank sum tests, Wilcoxon rank sum exact tests, and Kruskal-Wallis test. Results: A total of 55 journals were included; 6 (11%) were Gold OA (access to readers and large charge for authors), 2 (3.6%) were subscription (charge for readers and small/no charge for authors), 4 (7.3%) were delayed OA (reader access with no charge after embargo), and 43 (78%) were hybrid (author's choice). There was no significant difference between median APC for life sciences, medical, and surgical journals ($4,850 [$3,500-$8,900] vs. $4,592 [$3,500-$5,000] vs. $3,550 [$3,200-$3,860]; p = 0.054). The median US individual subscription costs (USD/Year) were significantly different for life sciences, medical, and surgical journals ($259 [$209-$282] vs. $365 [$212-$744] vs. $455 [$365-$573]; p = 0.038), and similar for international readers. A total of seventeen journals (42%) had a subscription price that was higher for international readers than for US readers. Conclusions: Most journals offer hybrid access services. Authors may be forced to choose between high cost with greater reach through OA and low cost with less reach publishing under the subscription model under current policies. International readers face higher costs. Such hindrances may be mitigated by a greater awareness and liberal utilization of OA policies.